Development and ergonomic evaluation of hand held vegetable seedling transplanter - Padmanathan, P K; Parimalam, P; Thambidurai, S; Nallakurumban, B; Arumuganathan, T (Plant Science Today, 2025)
Efficient vegetable production is essential to meeting growing food demands, requiring innovative solutions to reduce labor intensity and enhance productivity. Vegetable cultivation, especially for small farmers, demands innovative and affordable solutions to enhance productivity and reduce labor-intensive practices. The mechanization of agricultural processes has become increasingly important in reducing the physical strain and time-intensive nature of traditional farming operations, paving the way for innovative tools that enhance efficiency and user comfort. Transplanting of seedlings, a highly drudgery-oriented operation, is mainly performed by women. A hand held seedling transplanter has been designed and developed for transplanting vegetables seedlings based on the anthropometric dimensions of the user population. The number of seedlings transplanted per min using the handheld seedling transplanter ranged from 19 to 21, compared to 16 to18 using the conventional method. By using the hand held seedling transplanter, a significant reduction in the cost of operation was achieved, with 11.44 to 16.52% savings in cost reported. The average working heart rate while transplanting using the seedling transplanter was 103 bpm, compared to 120 bpm for conventional transplanting. The average energy expenditure while transplanting the seedlings using the seedling transplanter was 7.72 kJ min-1, compared to 10.94 kJ min-1. The performance evaluation of the designed transplanted indicted an increase in human productivity and a decrease in musculoskeletal discomfort during the transplanting process. The introduction of ergonomic and cost-effective solutions, such as the handheld seedling transplanter, not only improves productivity and reduces operational costs but also promotes sustainable practices while prioritizing the well-being of farmers.